Patient Education Strategies among Patients with Acute Myocardial Infarction: A Systematic Review - Huraini, Emil; Wahid, Irza; Machmud, Rizanda; Khatijah Lim, Abdullah * (Scientific Foundation SPIROSKI, 2022)
BACKGROUND: There is a need to summarize the effect of existing research-based education strategy on patients’ physical condition, health behaviour change, as well as psychosocial well-being in patients with acute myocardial infarction.